The Scenario of Buffalo Production and Research in Bangladesh - Habib, Md. Ahasan; Rahman, Md. Shahinur; Khatun, Asma; Ali, Md. Younus (Journal of Buffalo Science, 2023)
Background: This study aimed to characterize the scenario of buffalo production in the northern part of Bangladesh and review the published scientific literature on buffalo from Bangladesh. Methods: The study was conducted from August to December 2022. A draft questionnaire was prepared and modified before the final one based on the study's objectives. Data were collected through personal interviews with individual respondents. In addition, the review article was collected on buffalo from Google, Google Scholar, Research Gate, Scopus, Bangladesh Journal-Online (BJO), and PubMed. Results: Data was collected from 1099 animals from the northern part of the Natore and Lalmonirhat districts of Bangladesh. Most of the farmers were illiterate, and the age was above 40 years. Regarding the purpose of buffalo production, 69.16% (n=83) of the farmers narrated that they are motivated to milk with calves selling. The average herd size was about 9 and consisted of indigenous and crossbred buffaloes. Most of the farmers kept their buffalo in the Bathan. The coat color was predominantly black, with brown hair. Farmers 94.16% (n=113) practice de-worming, and the frequency was thrice a year. Wallowing is performed at least once a day in the pond or river for the thermal regulation of the buffalo. Among the farmers, 67.50% (n=81) have no training in rearing buffalo. Farmers practice natural mating by their own or neighbor bull to serve the heated cow. Sometimes it’s free, or sometimes, with payment on an average of BDT 400-500 or 3.79-4.73 US dollars. In some areas, AI is being practiced in buffalo under different organizations (LAL Teer, BRAC), and the cost of AI was recorded as about BDT 600-700 or 5.68-6.63 US dollars per cow. The average daily milk yield was 3.0 liter, whereas the lactation length was recorded at 179.9±3.84 days. The major constraints were high feed price 91.66% (n=110), shortage of land 41.08% (n=51), and lack of suitable marketing facilities 50.82% (n=62). 100% of farmers stated that they need improved grass production technology and reduced feed and medicine price; 24.16% (n=29) need good quality semen. From 2004 to 2022, 51 studies were found related to buffalo, where the highest 27.45% (n=14) belonged to performance studies, and 54.90% (n=28) studies were carried out in the southern part of Bangladesh. Conclusion: It can be concluded that buffalo has great potential with different areas of improvement. Therefore, more research is needed from different perspectives on production, reproduction, nutrition, quality of milk/meat/products, health, and sustainability of buffalo farming in Bangladesh.